Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M189/2 - Ziegler, Steffen; Kinne, Stefan; Schumacher, Mia; Wölfl, Anne-Cathrin (PANGAEA, 2023)
During M189/2 that took place in the Atlantic between 2023-05-16 and 2023-06-04, multibeam bathymetry raw data were recorded using the vessel's built-in Kongsberg EM122 echosounder. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data (zip file) and the cruise report for details.
Keywords: Bathymetry; Multibeam Echosounder